Systematic Literature Review: Efektivitas Pemecahan Masalah melalui Model Pembelajaran Inovatif - Klemens Mere (Journal on Education, 2023)
Learning according to this view is more a process of self-regulation in resolving cognitive conflicts that often arise through concrete experience, collaborative discourse, and interpretation. The purpose of this research is to analyze the effectiveness of problem solving through innovative learning models. The method used in qualitative research with library studies or System Literature Review (SLR). The purpose is to analyze the comparison of existing theories with previous theories in the research literature. The literature used is literature from research results or studies presented in scientific articles. All articles used were sourced from the electronic data literacy search engine Mendeley and Google Scholar. Based on the description of the results and discussion above, there are innovative learning models that can solve problems such as: Posing and Soving Learning Model, competency-based learning, problem-based learning, Group Science Learning model, simulation model learning and inquiry learning model.